THERMOMETER TELEMENTRI SYSTEM USING RADIO COMMUNICATION UNIT AS HANDHELD TRANSMITTER - Nurbaeti Nurbaeti; Ir. Irwan Nimara, MMSI Ir. Irwan Nimara, MMSI (Jurnal Sistem Komputer, 2000)
Radio Telemetry System was a system that serves to send a certain data from oneplace to another a distance away, using the radio wave transmission media.Remote temperature measurement (Telemetry Temperature) allows us to performmeasurements in inaccessible places or in areas dangerous to humans if directmeasurements of the area. One alternative to overcome this is to use radio telemetry.This transmitter system composed of several sub sections of the sensor, voltage tofrequency converters, and transmitter. The sensor converts the temperature scale tothe level voltage output is then compared to the voltage to frequency converter circuitwhich functions to change the sensor output voltage to the frequency scale.Modulated output to the transmitter circuit.